The Growing Cost of Deep Learning for Source Code: Attempting to mitigate problems associated with the trend toward massive dataset scaling. - Hellendoorn, Vincent J.; Sawant, Anand Ashok (Communications of the ACM, 2022)
The article opines on attempts to mitigate the problems engendered by massive dataset scaling with a focus on the costs of deep learning for source code. Costs associated with training artificial intelligences and artificial neural networks on a given computer model are identified. The author calls networking computing clusters to combine computing power, increase collaboration, and reduce costs.